UZBEK LANGUAGE AND INTERNATIONAL LANGUAGES: ISSUES OF MAINTAINING SEMANTIC ACCURACY IN TRANSLATION - Abduvaliyeva Shahnoza Abduvaliyevna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article examines the challenges of preserving semantic accuracy in translations between Uzbek and international languages, focusing on linguistic and cultural factors. The study identifies issues such as polysemy, morphological complexity, and syntactic differences that complicate accurate translations. Additionally, cultural nuances, including idiomatic expressions and honorifics, are analyzed as factors that influence meaning. The research highlights the limitations of current machine translation technologies and emphasizes the importance of human intervention in translation processes.